2004
DOI: 10.1124/jpet.104.078113
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Rapid Blood Clearance of Liposomes Containing Polyethylene Glycol-Lipid Conjugates and Nucleic Acid

Abstract: Polyethylene glycol (PEG) is used widely in the pharmaceutical industry to improve the pharmacokinetics and reduce the immunogenicity of therapeutic and diagnostic agents. The incorporation of lipid-conjugated PEG into liposomal drug delivery systems greatly enhances the circulation times of liposomes by providing a protective, steric barrier against interactions with plasma proteins and cells. Here we report that liposome compositions containing PEG-lipid derivatives and encapsulated antisense oligodeoxynucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
133
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(136 citation statements)
references
References 36 publications
(56 reference statements)
3
133
0
Order By: Relevance
“…Finally, after their accumulation, they are metabolized and eliminated by the target tissues. 5,92,93 Despite all the hopes invested in conventional liposomes, they have presented various problems and pharmacological implications over the years. A major drawback of conventional liposomes is their quick capture by the RES.…”
Section: Liposomes In Nanomedicinementioning
confidence: 99%
“…Finally, after their accumulation, they are metabolized and eliminated by the target tissues. 5,92,93 Despite all the hopes invested in conventional liposomes, they have presented various problems and pharmacological implications over the years. A major drawback of conventional liposomes is their quick capture by the RES.…”
Section: Liposomes In Nanomedicinementioning
confidence: 99%
“…When PEGylated liposome-encapsulated oligonucleotide, pDNA, or RNA is repeatedly injected into the mice, a strong immune response is induced. The circulation time of the preparation decreases, and the death rate of mice significantly increases (Semple et al, 2005). Thus, an in-depth investigation on the ABC phenomenon is necessary.…”
Section: Introductionmentioning
confidence: 99%
“…When covering lipoplexes by polyethyleneglycol (PEG) to reduce opsonisation and MPS uptake, a decrease of transfection efficiency was observed in vitro [9] and [10]. Moreover, it was shown that the use of PEG combined with liposomal formulations containing DNA makes them less efficient in vitro [9] and more immunogenic [11].…”
Section: Introductionmentioning
confidence: 99%